Wilajety irackie pod panowaniem tureckim na przełomie XIX i XX wieku - Jamsheer, Hassan A. (Acta Universitatis Lodziensis. Folia Historica, 1995)
The three wilayas of the Ottoman Empire: Bagdhad, Basra and Mosul, which in 1921 formed the Kingdom of Iraq, occupied an important position with reaspect to historical and strategic considerations as well as to discovery of petroleum resources in this area. It was, therefore, the object of great powers (Britain and Germany) rivarly. The inhabitants of the wilayas came from different nationalities and religious creeds, with muslim Arabs forming the greater majority (75%), followed by the Kurds (c. 20%). The despotic regime of Sultan Abdul-Hamid (1876-1909) met with opposition not only among non-Turkish nationals of the Empire, but also among the Turkish modernist movement of Yound Turkey. At first, the movement’s programme was progressive, accepting the idea of autonomy for non-Turks, but with the passage of time „Young Turks” returned to the earlier despotism and negation of national rigths of other nations. That was the case with respect to the Iraqi wilayas, where national cosciousness and orientation towards independence were gainig ground. Arab (and to some extent Kurdish) organisations of Iraqi lands were under the impact of different tendencies. Radical societies (as a rule, they were cladestine or emigrant) demanded sovereignty and were not inclined to compromise with ottoman authorities, while legal organisations had conciliatory attitudes. That was connected with anxiety about the possibility of being occupied by European powers, likewise North African Arab countries. Such was the case in the aftermanth of World War I.